PENGARUH PENYEBARLUASAN INFORMASI BADAN PENGELOLA (BAPEL) JAMKESDA TERHADAP KELUARGA MISKIN DI KABUPATEN SINJAI - Hermansyah, Hermansyah; Unde, Andi Alimuddin (KAREBA : Jurnal Ilmu Komunikasi, 2013)
Abstrak Sulitnya keluarga miskin mendapatkan informasi mengakibatkan pelayanan kesehatan tidak optimal dan maksimal, sehingga dibutuhkan adanya penyebarluasan informasi yang baik. Penelitian ini bertujuan untuk mengetahui (1) adanya pengaruh penyebarluasan informasi Badan Pengelola Jaminan Kesehatan Daerah terhadap keluarga Miskin di Kabupaten Sinjai., (2) adanya hubungan antara penggunaan media komunikasi dan isi pesan program Jamkesda dalam mempengaruhi perilaku keluarga Miskin di kabupaten Sinjai. Penelitian ini dilaksanakan di Kecamatan Sinjai Timur dan Kecamatan Sinjai Tengah Kabupaten Sinjai, dengan menggunakan Metode kuantitatif dengan sampel sebanyak 98 Responden Keluarga Miskin. Data dianalisis dengan menggunakan analisis statistik melalui pendekatan analisis regresi. Hasil penelitian dan uji statistik menunjukkan bahwa pengaruh penyebarluasan informasi Badan Pengelola Jamkesda terhadap keluarga miskin sebesar 77,3 %. Sebanyak 34,,8 % keluarga miskin dipengaruhi oleh penggunaan media komunikasi, dan 42,3 % keluarga miskin dipengaruhi oleh isi pesan program Jamkesda untuk dapat memanfaatkan program Jaminan Kesehatan Daerah, Sementara Hubungan penggunaan media Komunikasi dalam mempengaruhi perubahan perilaku keluarga miskin sebanyak 44,9 %, dan hubungan antara isi pesan program Jamkesda dalam mempengaruhi perubahan perilaku keluarga miskin diketahui sekitar 52,7 %. Hal ini menunjukkan bahwa pengaruh penyebarluasan informasi Badan Pengelola jamkesda terhadfap keluarga miskin sangat signifikan, sehingga tingkat pengetahuan, sikap dan perilaku keluarga miskin terhadap program jamkesda semakin tinggi untuk memanfaatkan program jamkesda sebagai investasi kesehatan bagi keluarga.Abstract This study aimed to determine (1) the effect of information dissemination Regional Health Insurance Management Board to poor families in Sinjai., (2) the relationship between the use of communication media and the message content Jamkesda program in influencing the behavior of poor families in the district Sinjai. The research was conducted in Sinjai, by taking the focus of research in the sub Sinjai Middle East and Sub Sinjai using quantitative methods with a sample of 98 respondents Poor Families. Data were analyzed using descriptive statistical analysis and regression analysis. The results showed that the effect of the dissemination of information to the Management Board Jamkesda poor knowledge level change through the use of the radio medium is found to be 38.7%. 27.6% change in attitude and behavior change of 29.6%. Meanwhile, through the Media Communication Group known effect on changes in knowledge level of 32.5%, Change of 36.7% on the attitude and behavior change of 39.8%. On the Use of Interpersonal Communication media influence on changing poor knowledge of 28.7%, 35.7% Changes in attitude and behavior change of 30.6%. While the contents of the message influence the terms of participation in the knowledge level of 28.7%, on attitudes andÂ behavior of 25.5% at 27.6%. Message service packs affect the knowledge by 32.6%, amounting to 34.7% in the attitudes and behaviors of 37.8%. Messages on the service system affects the level of knowledge of 22.4%, 24.5% Change of attitudes and behaviors by 23.4%. In the message referral system affects the level of knowledge was 16.3%, 15.3% attitude and behavior of 11.2%. While it is known that there is relationship communication media usage and message content in affecting change in the level of knowledge, attitudes and behavior of poor households of 61.9%. This suggests that the effect of the dissemination of information to the Management Board Jamkesda poor families is very significant, so that the level of knowledge, attitudes and behavior of poor families to the program to take advantage of the higher Jamkesda Jamkesda program as an investment for the health of the family.Â